Parents' Perceptions About Future Digital Parental Support—A Phenomenographic Interview Study - Bäckström, Caroline; Chamoun, Sandi; Tejani, Shazima; Larsson, Viveca (Frontiers in Digital Health, 2021)
Background: Parents use digital sources (such as the internet or online forums and applications) during pregnancy and after childbirth to receive informative support. Research shows that there is further need for innovation development in digital parental support despite informative support available in digital form. Purpose: To explore parents' perceptions of future digital parental support concerning pregnancy and the first 18 months of parenthood. Method: A phenomenographic interview study with an inductive approach including 15 semi-structured interviews was conducted. Results: The analysis process resulted in three descriptive categories: Opportunities for virtual and in-person meetings, Individualized digital parental support, and Professional knowledge and trustworthiness concerning future digital parental support. Conclusion: The results broaden the knowledge about how future digital parental support can be designed to facilitate the functional, interactive, and critical digital health literacy of new and would-be parents. To succeed, healthcare organizations should allow healthcare professionals to assume an active role in developing digital parental support, both as health educators (i.e., providing parents with knowledge) and facilitators (i.e., facilitating parents' use of digital parental support). However, parents perceived that future digital parental support should complement standard care instead of replacing in-person meetings with healthcare professionals.